Antimicrobial resistance in Vibrio cholerae O1/O139 clinical isolates: a systematic review and meta-analysis. Issue 9 (2nd September 2022) - Liu, Chaoying; Wang, Ye; Azizian, Khalil; Omidi, Nazanin; Hassan Kaviar, Vahab; Kouhsari, Ebrahim; Maleki, Abbas
ABSTRACT: Objectives: Vibrio cholerae O1/O139 is responsible for cholera epidemics that remains a huge public health menace across the globe. Furthermore, an increasing resistance rate among V. cholerae strains has been reported around the world. Therefore, the objective of this meta-analysis was to evaluate the weighted pooled resistance (WPR) rates in clinical V. cholerae O1/O139 isolates based on different years, areas, antimicrobial susceptibility testing, and resistance rates. Research design and methods: We searched the studies in PubMed, Scopus, Embase, and Web of Science (until January 2020). Statistical analyses were conducted using STATA software (ver. 14.0). Results: A total of 139 studies investigating 24, 062 V. cholerae O1/O139 isolates were analyzed. The majority of the studies originated in Asia ( n = 102). The WPR rates were as follows: azithromycin 1%, erythromycin 36%, ciprofloxacin 3%, cotrimoxazole 79%, doxycycline 7%, and tetracycline 20%. There was increased resistance to cotrimoxazole, ciprofloxacin, and tetracycline during the 1980–2020 years. Conclusions: Temporal changes in antibiotic resistance rate found in this study demonstrated the critical continuous surveillance of antibiotic resistance. Also, ciprofloxacin, azithromycin, gentamicin, cephalexin, imipenem, ofloxacin, and norfloxacin were found to be the best antibiotics against V. cholera, with the highest and the lowest effectiveness resistance rate.